Four new triterpene glucosides from Salacia cochinchinensis Lour. Issue 9 (3rd May 2022) - Gao, Lu; Duan, Li-Kun; Feng, Jin-E; Jiang, Yun-Tao; Gao, Jun; Fan, Jun-Ting; Dai, Rong; Jiang, Zhi-Yong
Abstract: Four new triterpene glucosides (1–4 ) were isolated from the 90% ethanol extract of Salacia cochinchinensis, together with five known compounds (5–9 ). The structures of the new compounds were elucidated by comprehensive spectroscopic analysis including HRESIMS, IR, 1 D and 2 D NMR analysis. All isolates were assayed for their α-glucosidase inhibitory activity. Compound 9 showed remarkable α-glucosidase inhibitory activity with an IC50 value of 0.31 μM, and the triterpene glycosides (1 –5 ) exhibited moderate α-glucosidase inhibitory activity. Graphical Abstract: